Pemberdayaan UMKM Pariwisata Melalui Literasi Pariwisata Berkelanjutan dan Pengelolaan Sampah Terpilah di Desa Sukadiri Kabupaten Tangerang - Isaghoji; Raden Asri Kartini; Adrial (jurnal ABDIMAS Indonesia, 2025)
The Community Service Program (Kuliah Kerja Nyata / KKN) of Universitas Muhammadiyah Tangerang (UMT) in Sukadiri Village, Tangerang Regency, was implemented with the aim of empowering the community through strengthening tourism-based MSMEs and raising environmental awareness. This program employed a participatory qualitative descriptive approach, in which students acted as facilitators in assisting the community. The main focus included sustainable tourism literacy, MSME digitalization, waste segregation management, and community literacy improvement. Key activities carried out consisted of designing logos and digital branding for MSMEs, conducting ecoprinting training utilizing local flora, delivering legal counseling on bullying within the scope of the Electronic Information and Transactions Law (ITE), creating educational boards and segregated waste bins, establishing a reading corner, and supporting food security through corn planting. The results indicated increased community awareness of environmental management, improved skills of MSME actors in utilizing digital technology, and the growth of literacy culture among children and youth. In addition to providing tangible benefits for the community, this program also enriched students’ experiences in applying their academic knowledge directly in the field. Therefore, the KKN in Sukadiri Village not only contributed to sustainable village development but also served as a best practice model that could be replicated in other regions.